A Comparison of Fabry–Perot Interferometer and Meteor Radar Wind Measurements Near the Polar Mesopause Region. Issue 4 (28th April 2021) - Lee, Changsup; Jee, Geonhwa; Kam, Hosik; Wu, Qian; Ham, Young‐Bae; Kim, Yong Ha; Kim, Jeong‐Han
Abstract: The neutral winds in the Mesosphere and Lower Thermosphere (MLT) region have been observed at King Sejong Station, Antarctica using a meteor radar (MR) and a Fabry–Perot interferometer (FPI) simultaneously. These two independent MLT wind measurements are compared to each other to identify the characteristics of FPI measurement. Instead of using a fixed emission height for FPI winds, for the first time, we consider the temporal variations of airglow emission layer in association with corresponding meteor height distributions for more accurate comparison between the FPI and MR winds. The temporal variations of the airglow emission layers are examined from the inverse relationship between the height integrated emission rate and the peak emission height derived from the TIMED/SABER observations. It is found that FPI winds are consistently smaller than MR winds and the discrepancy becomes larger for OI emission at higher altitude, which may be related to large wind shear in the MLT region and variabilities of the emission layers. Finally, we found that the FPI can provide reliable height‐averaged winds in the MLT region where existing a strong wind shear from this simultaneous MR wind measurements. Plain Language Summary: Simultaneous but independent observations of the MLT winds from the Fabry–Perot interferometer (FPI) and meteor radar (MR) are compared to each other to study on the characteristics of the wind measurements in the MLT region. For the first time, we used height distributions of meteor echoes to estimate the height of the OH airglow emission layers, which enables us to perform a more accurate comparison of the two measurements compared with using a fixed emission layer height. It is found that the FPI winds are consistently smaller than the MR winds and the discrepancies become larger for OI emission layer at higher altitude. However, it is also confirmed that the FPI wind measurements in the MLT region can still provide reliable winds even under the strong wind shear in the region. Key Points: Temporal variations of airglow emission layers, rather than fixed emission heights, are considered for more accurate wind comparison FPI winds are consistently smaller than MR winds and the larger discrepancies occur for OI emission layer at higher altitude The FPI can provide reliable height‐averaged winds even under a strong wind shear near the mesopause region